Evaluating a Local Economic Empowerment Grant: Growth in Cooperative Capital, Membership, and Net Surplus - Aurora Andi Tribuana; Bayu Priambodo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Cooperatives play a strategic role in community-based economic development in Indonesia but often face constraints related to capital, human resources, and institutional sustainability. Specific Background: To address these challenges, the Kediri City Government implemented the PRODAMAS Plus Community Empowerment Program, providing grants to strengthen RW-level cooperatives, including the Kemiri Makmur Cooperative. Knowledge Gap: Despite the widespread implementation of grant-based empowerment programs, empirical evidence on their effectiveness in ensuring long-term cooperative sustainability at the grassroots level remains limited. Aims: This study aims to evaluate the effectiveness of the PRODAMAS Plus economic grant in supporting the sustainability of the Kemiri Makmur Cooperative using Steers’ effectiveness framework. Results: The findings demonstrate that the grant significantly increased cooperative capital, assets, membership, and net surplus (SHU), enhanced service delivery, and enabled short-term business innovation, although sustainability was constrained by limited human resources, space, and leadership regeneration. Novelty: This study provides micro-level evidence of how localized fiscal empowerment influences cooperative performance across multiple effectiveness dimensions. Implications: The results suggest that grant programs should be complemented with continuous mentoring, capacity building, and institutional strengthening to ensure sustained community economic development. Highlights: Grant Impact: Substantial government grants significantly strengthened cooperative capital, assets, and net surplus. Institutional Capacity: Human resource limitations and leadership regeneration remain key challenges to sustainability. Policy Insight: Financial assistance must be integrated with continuous mentoring and capacity building to ensure long-term effectiveness. Keywords: PRODAMAS Plus, Cooperative Sustainability, Community Empowerment, Local Economic Development, Program Effectiveness